Using technology to support learning and teaching - Fisher, Andy, 1976-; Exley, Kate 1964-; Ciobanu, Dragos (London : New York Routledge, Taylor & Francis Group, 2014)
"The climate of Higher Education is changing rapidly. Students are more likely to see themselves as consumers and have increasingly high expectations regarding teaching and learning. The use of new technology is, in part, being used to meet this need whether by increased access to teaching materials outside the classroom or the use of interactivity in lectures. Although there is no illusion amongst Higher Education institutions that technology is a panacea, it is clear that technology is a vital tool in meeting expectations and one that will be used more and more. Using Technology to Support Learning and Teaching fills a gap in the market by provides a jargon free (but pedagogically informed) set of guidance for teaching practitioners who wish to consider the variety of ways in which technology can enrich their practice and the learning of their students. It integrates a wide range of example cases from different kinds of HE institutions and different academic disciplines, illustrating pedagogies that are easily practicable. Full of advice, hints and tips for practitioners who want to use technology to support a style of teaching and learning that is built on sound pedagogical principles, it provides a quick user-friendly reference on how to incorporate technology into Higher Education in a way that adheres to their learning principles and values"
Learning theory and the use of technology in HE -- Inclusive practice : disability and diversity -- Collaboration and networking : the use of social media -- Technology for interaction -- Technology for assessment and feedback -- Podcasting and vodcasting -- Virtual learning environments -- Open source -- Immersive 3D online environments -- Future developments.
Includes bibliographical references (pages 214-222) and index.
Keywords: Information technology -- Study and teaching (Higher)